Examining the influence of current waveform on the lightning electromagnetic field at the altitude of halo formation. (August 2019) - Ren, Huan; Tian, Ye; Lu, Gaopeng; Zhang, Yunfeng; Fan, Yanfeng; Jiang, Rubin; Liu, Mingyuan; Li, Dongshuai; Li, Xiao; Qie, Xiushu
Abstract: In this paper, we extend the analysis of Lu (2006) to calculate the electric field ( E -field) of lightning return stroke in the region of sprite initiation and halos using a transmission line model that uses various lightning stroke current measured during the triggered lightning experiment as the driving source to examine the individual components (i.e., electrostatic, induction, and radiation) of E -field perturbation. As the altitude increases, the maximum strength of electrostatic and induction field gradually decreases, and the induction field decays slower than electrostatic field above 80 km. The electrostatic and induction field in the region of halo formation have a much larger contribution to the total E -field than the radiation field. Therefore, it is proposed that in addition to the electrostatic field, the induction field (with amplitude more than half of total E -field) is the main component of the total E -field within the first half millisecond directly above the stroke. Our analysis indicates that the induction field might play a significant role in the halo formation and probably also the sprite initiation. The M -component, the longer rising edge, the wavy long tail, and the relatively long time scale of stroke current can increase the amplitude of electrostatic and induction field at the height of halos, and drive the occurrence of halos and the subsequent development of streamers, therefore forming sprites. Our results enrich the understanding on the mechanism of halo production and the lightning electromagnetic field in the middle and high-altitude atmosphere, and also pave the way for future accurate modeling of halo formation. Highlights: Various lightning stroke currents with a relative long time scale measured during the triggered lightning experiment are used as the driving source to calculate the E -field generated by the lightning return stroke. Different from the work of Pasko et al. (1995) (using the full-wave method), this paper selects the classical dipole method which can well represent the field components(i.e., electrostatic, induction, and radiation) to study the mechanism of halo formation. This paper puts forward that in addition to the contribution of the E -field generated by the charge itself (electrostatic field) to the initiation of halo, the influence of induction field induced at high altitude from the process of charge movement on the initiation of halo cannot be ignored.